Heterogeneous Detection of A-antigen on von Willebrand Factor Derived from Platelets, Endothelial Cells and Plasma - Brown, Simon A.; Collins, Peter W.; Bowen, Derrick J. (Thrombosis and Haemostasis, 2002)
The exact function of the carbohydrate component of von Willebrand factor (VWF) is unknown. ABO blood group antigens are present as integral structures on the oligosaccharide side chains and it has long been recognised that ABO blood group is a determinant of VWF levels. The mechanism for this is not known. Using a monoclonal antibody against the A-antigen, we investigated the presence of this antigen on VWF from plasma, platelets, human umbilical vein endothelial cells (HUVEC) and saphenous vein endothelial cells. Initial studies on plasma VWF revealed that 23.5% of samples appeared to be negative for the A-antigen. This was shown to correlate with the A2 subtype of the A-antigen (p <0.01). Analysis of intracellular VWF from saphenous vein endothelial cells revealed low levels of A-antigen to be present in comparison to the corresponding plasma VWF. In contrast, VWF from platelets and HUVEC gave no detectable A-antigen. However, within 1 h of administration of DDAVP to type 1 VWD patients, there was a >2-fold increase in the A-antigen/VWF:Ag ratio for VWF in the plasma. In vitro experiments with serum N-acetlygalactosaminyltransferase failed to demonstrate any addition of A-antigen to platelet or HUVEC VWF. These data are consistent with heterogeneity in the content of A-antigen on VWF from different physiological compartments. Also, they are consistent with either a change in the A-antigen content of VWF after release from the intracellular compartment or a difference in the intracellular addition of A-antigen to VWF by endothelium from different vascular beds.
Keywords: von Willebrand factor; ABO blood group; platelet; endothelial cell; DDAVP